Growth and Yield of Celery (Apium Graveolens L.) in Organic Cultivation on Alluvial Soil - Agnes Tutik Purwani Irianti; Sri Rahayu; Agus Suyanto; Rosalina Yuliana Ayen; Sherly Oktarianti (The University of Lampung, 2024)
Celery (Apium graveolens L.) is a horticultural crop that is consumable and offers numerous health benefits. The purpose of this study was to ascertain how celery growth and yield cultivated on alluvial soil were affected by the interaction between liquid organic NPK fertilizer and chicken manure. The study utilized a field experiment that was designed completely randomized comprising two factors. The first factor was the dosage of chicken manure with three levels: C1: 50 g/pot, C2: 100 g/pot, and C3: 150 g/pot. The second factor was liquid organic NPK fertilizer with three levels: L1: 1%, L2: 2%, and L3: 3%. All treatment combinations were performed in triplicates. The results indicated that the interaction between chicken manure and liquid organic NPK fertilizer significantly affected the number of tillers and dry weight of celery yield. Chicken manure as a single factor significantly influenced the number of stems and tillers. Liquid organic NPK fertilizer as a single factor significantly influenced the number of tillers, fresh weight, dry weight, and plant height. The combination of chicken manure and liquid organic NPK fertilizer (C1L3) produced the highest number of stems per clump (79.44 stems) and the highest number of tillers per clump (9.78 tillers). The combination of C2L3 yielded the highest fresh weight (184 g) and dry weight (17.33 g). Keywords: Alluvial soil, Celery, Chicken manure, Liquid organic NPK fertilizer